Answer:
Step-by-step explanation:
Circle of center A(2, 0) and radius r.
P (22, 15), Q(−13, c) and R (k, 24) all lie on a circle,
[tex]r=AP=\sqrt{\left( 22-2\right)^{2} +\left( 15-0\right)^{2} }[/tex]
[tex]=25[/tex]
Q(−13, c) lies on the circle then ,
[tex]AQ=r\Longrightarrow AQ^{2}=r^{2}\Longrightarrow (-13-2)^{2}+(c-0)^2=25^2=625[/tex]
[tex]\Longrightarrow 225+c^{2}=625[/tex]
[tex]\Longrightarrow c=20[/tex]
R (k, 24) lies on the circle then ,
[tex]AR=r\Longrightarrow AR^{2}=r^{2}\Longrightarrow (k-2)^{2}+(24-0)^2=25^2=625[/tex]
[tex]\Longrightarrow (k-2)^{2}+576=625[/tex]
[tex]\Longrightarrow (k-2)^{2}=49[/tex]
[tex]\Longrightarrow k-2=7\ \ or \ \ k-2=-7[/tex]
[tex]\Longrightarrow k=9\ \ or \ \ k=-5[/tex]